KLEINE – LEVIN SYNDROME (A Case Report) - RAJU, MSVK (Med J Armed Forces India, 1994)
A 30 year old male soldier suffered from five episodes of hypersomnia. Each episode was associated with megaphagia, mental confusion, irritability, coenesthopathic hallucinations and sexual disinhibition. The average duration of each episode was ten weeks with symptomfree intervals ranging from two weeks to one year. The patient responded well to treatment with carbamazepine and fenfluramine.